Maxillary second molar from the Rozhok I Micoquian site (Azov Sea region): Another link between Eastern Europe and Siberia. Issue 168 (July 2022) - Zubova, Alisa V.; Moiseyev, Vyacheslav G.; Kulkov, Alexander M.; Otcherednoy, Aleksander K.; Markin, Sergey V.; Kolobova, Ksenia A.
Highlights: The molar from the Middle Paleolithic site of Rozhok I is a Neanderthal. The migration of the Micoquian from Europe to Asia passed through the Azov Sea region. Analysis of the crown diameters revealed a similarity between Eastern Micoquians.